Job crafting, positive psychological capital, and social support as predictors of job embeddedness on among clinical nurses- a structural model design - Mi-Soon Yun; Miyoung Lee; Eun-Hi Choi (BMC Nursing, 2024)
Abstract Background This study establishes the relationships among role conflict, positive psychological capital, social support, job crafting, and job embeddedness among clinical nurses. The results are expected to provide a basis for efficient human resource management in hospitals. Methods Considering a 15% dropout rate, we distributed 300 copies of our questionnaire, of which 290 were returned. We used 260 responses in the final analysis after excluding 40 responses that were incomplete or showed an identical pattern in the item responses. Participants were clinical nurses with less than one year of experience in general and tertiary general hospitals in G province and D metropolitan city in South Korea. A structured questionnaire was administered from January 10 to February 28, 2022. The collected data were analyzed using SPSS 26.0 and AMOS 26.0. We assessed the statistical significance using the bootstrapping method. Results The direct and total effects (both β = 0.806, p =.007) of positive psychological capital on job crafting were significant. The direct and total effects (both β = 0.451, p =.004) of social support on job crafting were significant. The direct (γ = 0.292, p =.055), indirect (γ = -. 671, p =.003), and total (γ = − 0.379, p =.008) effects of role conflict on job crafting were significant. The direct (γ = − 0.382, p =.007), indirect (γ = − 0.208 p =.003), and total (γ = − 0.589, p =.006) effects of role conflict on job embeddedness were significant. The direct and total (both β = 0.548, p =.005) effects of job crafting on job embeddedness were significant. Conclusions Nurses’ job embeddedness is directly influenced by their job crafting, which is shaped by high levels of positive psychological capital and social support. When job crafting takes place, role conflict increases, and if job crafting becomes difficult because of severe role conflict, job embeddedness decreases. Therefore, to increase job embeddedness among clinical nurses, hospitals must implement support systems and programs to increase job autonomy, and positive psychological capital to promote job crafting.